Invariants of nonlinear evolution type equations and their exact solutions - Ngubane, Sizwe Remington (My University, 2006)
The role of invariants in obtaining exact solutions of dierential equations is reviewed. The examples considered are nonlinear evolution type equations like the Fisher and Fitzhugh-Nagumo equations. Finally, we look directly at an equation (formulated) governing some non-Newtonian uid in a rotating system.
Student Number : 9701675D - MSc dissertation - School of Mathematics - Faculty of Science
Keywords: invariants; evolution equaitons